Do investments respond to taxation and incentives? evidence from the Philippines - Quimbo, Stella A.
In this paper, accelerator models are estimated to assess the responsiveness of industry investments to changes in tax rates and incentives. The cross-sectional analysis uses data from the 2009 and 2010 waves of the Annual Survey of Philippine Business and Industry covering 27,575 and 29,298 firms, respectively, spread over 942 industry subclasses. This data set is supplemented by administrative data on fiscal incentives. The results show that tax rates and incentives can explain inter-industry variations in investments levels. The investment-tax and investment-subsidy relationships are found to be non-linear. Reduced taxes predict higher investments, with larger effects for industry groups that already have previous investments. Increased incentives predict larger investments, with the investment effects varying in size across industries. A modified version of the model, which was estimated using time-series data from 1973 to 2014, validated the study's cross-section results. The findings lend support to current legislative initiatives to lower incorporate income tax rates and rationalize fiscal incentives.
Keywords: Corporate income tax; Fiscal incentives; Investments; Subsidies